Ravni cen storitev v Sloveniji in Belgiji - Zorin, Marjeta (Gospodarska gibanja, 2010)
This paper aims to show the results of our analysis, within we have compared prices of 100 services between Slovenia and Belgium. We have found out that the price level of services in Slovenia were in February 2009 on average by 33% lower than in Belgium. Financial and other services were the most expensive among research groups of services in Slovenia. This group of services was by 30 % more expensive than the average of all prices of services in Slovenia (the price parity was 0.87). The next were passenger transport services with price parity of 0.79. Relatively the cheapest were municipal services with price parity of 0.34 (49 % cheaper than the average of all prices of services in Slovenia). They were followed by public care services with the price parity of 0.48. Although the prices of services in Belgium are generally higher, the price disparities of services between Slovenia and Belgium remain substantial. This indicates that the process of price convergence is comparatively weak in services and probably marked by irregular functioning of individual submarkets. The difference in aggregate price level of services is also reflected in a lower relative purchasing power of average net wages in the service sector of Slovenia.
Keywords: Belgija; cene; kupna moč; Slovenija; storitve